Kinetics of used waste cooking oil methanolysis catalyzed by heterogeneous waste catalyst - Sulaiman, Sarina; Amin, M. H. M. (2015)
Biodiesel provides a solution as an alternative source to replace the depleting fossil fuel. Along with the measurable reduction in pollution emission, burning biodiesel also reduces the offensive odour associated with diesel or heating oil combustion. Producing biodiesel from wasted cooking oil most likely achieves the highest energy balance of all because the raw material is a waste product. The main objective of this research is to investigate the kinetic of used vegetable oil methanolysis catalyzed by heterogeneous waste. Fish bone waste was used as a catalyst for the methanolysis of waste cooking oil. The effects of temperature and catalyst amount were varied between 50˚C - 65˚C and 4 - 10 wt % respectively. The highest yield of biodiesel, 84.5 % were achieved at 6 wt % of catalyst amount, mixing of 300 rpm, methanol to oil ratio of 18:1 and reaction temperature of 65˚C.